(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Diabetes mellitus (DM) is the most common metabolic disorder affecting the people worldwide. Even though diabetes has been known since antiquity, only in the last few decades new discoveries have provided great hopes to minimize morbidity and mortality. It is estimated that for one diagnosed diabetes there is undetected diabetes. Diabetic ketoacidosis, a major fatal complication of diabetes has virtually come down with advent of insulin. However, the vascular complications have remained the same and they have replaced diabetic ketoacidosis as the frequent cause death in diabetes.